INTRODUCTION TO PREDICTIVE, PREVENTIVE AND PERSONALIZED MEDICINE: PAST EXPERIENCE AND FUTURE REALITY - S. V. Suchkov; N. V. Stavitskaya; A. Notkins; Yu. M. Lopukhin; F. Bunz; Yu. V. Belov; K. Payne; J. Creeden; T. A. Bodrova; V. Costiglioli; H. Abe; O. Golubnichaja (Туберкулез и болезни лёгких)
.